Kosta vad det kosta vill - perfekt ska det va! -En kvalitativ studie av gymnasieelevers upplevelser av perfektionism - Blomberg,Martin; Jönsson,Ann-Sofie (2018)
The purpose of the study was to gain an in-depth understanding of upper secondary school's own experiences of how high degree of perfectionism is affecting their mental health. Selection of informants took place with surveys, where their degree of perfectionism was estimated. Semi-structured interviews were conducted with eight high school students studying in academic preparatory programs. The collected data was analyzed with thematic analysis, with twelve themes chosen. A considerable finding is that the collected self-estimates showed a major deviation from the norm-population, where the high school students in this study estimated significantly higher than the US comparative population regarding perfectionism. Another conclusion is the importance of social factors for the origin and maintenance of perfectionism. Several informants with high degree of perfectionism expressed strong experiences of negative affect related to achievement and failure. Informants also had difficulty with personal boundaries, which led to neglect of basic needs. Cultural differences were seen to play a role in relation to perfectionism. In relation to results and conclusions, implications for future research were discussed.
Keywords: Perfectionism; Thematic Analysis; Social Factors; Maintenance; Negative Emotions; Fear of Failure and Limitation.